Retrospective study showed that palpitations with tachycardia on admission to a paediatric emergency department were related to cardiac arrhythmias. - Bobbo, Marco; Amoroso, Stefano; Tamaro, Gianluca; Gesuete, Valentina; D'agata Mottolese, Biancamaria; Barbi, Egidio; Ventura, Alessandro (Acta Paediatr, 2019)
AIM: This retrospective study reviewed the prevalence and long-term prognosis of children aged 0-18 with palpitations who were admitted to the emergency department (ED) of an Italian paediatric hospital. METHODS: We examined all admissions to the ED of the IRCCS Burlo Garofolo between January 2009 and December 2015 by selecting triage diagnoses of palpitations. The hospital discharge cards were reviewed to assess vital parameters, physical examinations, diagnostic tests, cardiology consultations and final diagnoses. RESULTS: Of the 142 803 patients who attended our ED for any reason, 96 (0.07%) complained of palpitations. Despite this low prevalence, it was noteworthy that 13.5% had a real underlying arrhythmic cause and needed medical assistance. Over half (52.1%) were women and the mean age was 12.7 years. At the long-term follow-up, at a mean of 47 ± 23 months, 53.8% of patients with a cardiac arrhythmia had received medical therapy and 46.1% had undergone trans-catheter ablation for supraventricular tachycardia. A heart rate above 146 beats per minute or palpitations for more than an hour was statistically related to a cardiac arrhythmia. CONCLUSION: Palpitations were an infrequent cause of admission to our ED, but 13.5% who displayed them had an underlying cardiac arrhythmia.